Artificial substrata in a shallow sublittoral habitat: do they adequately represent natural habitats or the local species pool? - Smith, Stephen D.A; Rule, Michael J (Journal of experimental marine biology and ecology, 2002)
Artificial substrata have been advocated as tools which have considerable potential for monitoring both natural and anthropogenic effects on invertebrate communities of shallow coastal environments. In this experiment, community structure was compared between two dominant natural algal habitats (kelp holdfasts and algal turf) and artificial substratum units (ASUs; nests of pan scourers) deployed in close contact with, and 20 cm above the substratum. Univariate and multivariate statistical analyses were applied to the data to determine the similarity of community structure between the four different habitats. In addition, recently developed measures of taxonomic distinctness were applied to the data from both sets of artificial substrata to determine if they provided a representative sample of the local epifaunal species pool and thus have the potential to be used as surrogate samples for this important faunal group. There were marked differences between community structure in each of the habitats. Both sets of artificial substrata were dominated by tubicolous polychaetes with abundances that were more than an order of magnitude greater than in the holdfast and turf samples. The fauna recruiting to the artificial substrata deployed above the substratum showed the lowest values in the univariate summaries of diversity and evenness and were unrepresentative of the local species pool. Artificial samples deployed in contact with the substratum showed greater diversity and evenness but were still mostly unrepresentative of the local species pool. The tendency for both sets of artificial substrata to under-sample amphipods and to be dominated by suspension-feeding polychaetes suggests that methods using these units may be relatively insensitive to the effects of anthropogenic impacts (e.g. sewage outfalls) where shifts in community structure including increased dominance of suspension-feeders and polychaetes and a reduced dominance of amphipods have been observed. Further studies, including the evaluation of temporal variation in community structure related to the time at which the ASUs are deployed and duration of deployment, are needed to test the wider utility of artificial substrata as tools for monitoring shallow, sublittoral, epifaunal communities.